ANALYSIS OF HUMAN RESOURCES MANAGEMENT IN INCREASING THE PERFORMANCE OF STATE MADRASAH ALIYAH TEACHERS IN RIAU PROVINCE - Dupni; Ahmad Shukri; Minnah El Widdah (European Journal of Humanities and Educational Advancements, 2023)
The aim of the study was to determine the analysis of human resource management in improving the performance of teachers of State Aliyah Madrasas in Riau Province. This descriptive qualitative research uses a case study approach and collects data using observation, interview, and documentation techniques. Place of research at Madrasah Aliyah Negeri in Riau Province. The research subjects consisted of madrasa heads, teachers, administrative staff and students.The results of the research are that the causes of teacher performance at MAN in Riau Province tend to decrease because work standards are not applied consistently, so that their implementation faces many problems and challenges according to the internal and external conditions of the madrasa. The performance of MAN teachers in Riau Province has not prioritized work values according to the vision and mission of the existing madrasas. In practice, teachers have been working normatively for a long time according to customs and rules, but minimal innovation. So that in practice they do not yet have achievements that are in accordance with madrasah work standards according to the expectations of the public or users. Management of madrasah heads in improving the performance of MAN teachers in Riau Province in accordance with their abilities and educational qualifications, in working and familiarizing their subordinates with clear and planned work patterns with due regard to discipline, cooperation and obedience to government regulations and having adequate teaching performance. The head of the madrasa also supervises and evaluates the work of teachers to ensure the implementation of a positive culture in working in the madrasa environment. The conclusion of this study is that the analysis of human resource management in improving the performance of teachers of State Madrasah Aliyah in Riau Province has been carried out, although it is not optimal because the HRM model of teacher performance is still centralized.